Implementasi Alat Pelindung Diri Sebagai Esensi K3 Pada Pekerja Las Konstruksi di UMKM - Rian Prasetyo; Rahmatul Ahya; Mathilda Sri Lestari; Ainur Komariah (Universitas Islam Indonesia, 2024)
Occupational safety and health (K3) is very important. There are various types and levels of employment sectors in Indonesia, one of which is in the MSME (Micro, Small and Medium Enterprises) sector which is engaged in the welding service sector. Based on observations made at UMKM